Ancient genomes reveal origin and rapid trans-Eurasian migration of 7th century Avar elites - Gnecchi-Ruscone, Guido Alberto; Szécsényi-Nagy, Anna; Koncz, István; Csiky, Gergely; Rácz, Zsófia; Rohrlach, A B; Brandt, Guido; Rohland, Nadin; Csáky, Veronika; Cheronet, Olivia; Szeifert, Bea; Rácz, Tibor Ákos; et al. (Cell, 2022)
The Avars settled the Carpathian Basin in 567/68 CE, establishing an empire lasting over 200 years. Who they were and where they came from is highly debated. Contemporaries have disagreed about whether they were, as they claimed, the direct successors of the Mongolian Steppe Rouran empire that was destroyed by the Turks in ∼550 CE. Here, we analyze new genome-wide data from 66 pre-Avar and Avar-period Carpathian Basin individuals, including the 8 richest Avar-period burials and further elite sites from Avar's empire core region. Our results provide support for a rapid long-distance trans-Eurasian migration of Avar-period elites. These individuals carried Northeast Asian ancestry matching the profile of preceding Mongolian Steppe populations, particularly a genome available from the Rouran period. Some of the later elite individuals carried an additional non-local ancestry component broadly matching the steppe, which could point to a later migration or reflect greater genetic diversity within the initial migrant population.
Keywords: DNA, Ancient; migrace lidstva; populační genetika; human migration; migration period; Genetics, Population; population genomics; Avars; Sulfur; early medieval; History, Ancient; Pannonia; dějiny starověku; Human Migration; genom; ancient DNA; starobylá DNA; lidé; Humans; Carpathian Basin; Genome; Asian People; Asijci; síra; steppe nomads